ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL PEMODERASI - Destia Kusuma; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2014)
The aim of this research is to find empirical proof about the effect CSR on corporate financial performance and the effect CSR on corporate financial performance in the future that moderated by earning management. CSR disclosure by GRI G3 is used as the proxy of CSR activity, ROE is used as the proxy of financial performance and discretionary accruals by The Modified Jones model is used as the proxy of earning management practices. Sample used in this research were 27 companies participated on Indonesia Sustainability Reporting Award (ISRA) during 2009-2011 and listed on Indonesia Stock Exchange (IDX) over 2008-2010. The analysis methods of this research use simple regression analysis for hypothesis 1 and multiple regression analysis with the Absolute Residual Method for hypothesis 2. The results of this research show that CSR has no significant influence on corporate financial performance. The analysis with the moderating variable Absolute Residual Method shows that earning management moderate in relation between CSR and corporate financial performance and it shows negative significant influence.